2021
DOI: 10.1016/j.jmig.2020.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Natural Orifice Transluminal Endoscopic Surgery for Tubal Stump Pregnancy

Abstract: Objective: To demonstrate a case of left tubal stump pregnancy successfully treated using our 2-step technique for transvaginal natural orifice transluminal endoscopic surgery (vNOTES). Design: Demonstration of the technique using surgical video footage. Setting: Tertiary university hospital. Interventions: A 27-year-old gravida 3 para 0 patient with a history of laparotomy, left salpingectomy owing to a ruptured tubal pregnancy, was referred to our hospital because of a pregnancy of unknown location. Her seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The transvaginal natural orifice transluminal endoscopic surgery (vNOTES) is a new minimally invasive procedure (MIP) in which the vagina is used as a natural access to the peritoneal cavity and enables endoscopic surgery with conventional laparoscopic instruments. Several studies have demonstrated the feasibility and safety on vNOTES with many advantages leading to a day-care or ambulatory procedure: reduced immediate postoperative pain, faster postoperative recovery, better cosmetic results without skin scar, high patient satisfaction [1][2][3][4][5][6][7][8][9][10][11]. Some studies have also shown the superiority of vNOTES in comparison with the classical laparoscopic surgery in term of lower postoperative pain scores and the absence of trocar-site complications [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The transvaginal natural orifice transluminal endoscopic surgery (vNOTES) is a new minimally invasive procedure (MIP) in which the vagina is used as a natural access to the peritoneal cavity and enables endoscopic surgery with conventional laparoscopic instruments. Several studies have demonstrated the feasibility and safety on vNOTES with many advantages leading to a day-care or ambulatory procedure: reduced immediate postoperative pain, faster postoperative recovery, better cosmetic results without skin scar, high patient satisfaction [1][2][3][4][5][6][7][8][9][10][11]. Some studies have also shown the superiority of vNOTES in comparison with the classical laparoscopic surgery in term of lower postoperative pain scores and the absence of trocar-site complications [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported successfully using vNOTES to manage tubal ectopic pregnancy, adnexal torsion, ovarian cyst rupture, and pelvic inflammatory disease [1] , [2] , [3] , [8] , [12] . Similarly, we were able to manage gynecological (ectopic pregnancies, adnexal torsions, painful ovarian cysts, post-hysterectomy hemoperitoneum, and uncontrollable uterine bleeding) and non-gynecological (appendicitis) emergencies by vNOTES in 17 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, minimally invasive techniques have been increasingly used in emergency surgery, considerably reducing the morbidity associated with open approaches. To minimize surgical morbidity further, some authors proposed to manage gynecological emergencies by transvaginal natural orifice transluminal endoscopic surgery (vNOTES) [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%